Tensile bond strength of composite luting cements to metal alloys after various surface treatments - Denizoglu Saip; Hanyaloglu Cem; Aksakal Bunyamin (Wolters Kluwer Medknow Publications, 2009)
Aims: To evaluate the effects of two different surface treatments and bonding agents on tensile bond strength between a Co-Cr and a Ni-Cr cast alloy and two resin-luting cements. Materials and Methods: Two hundred and forty alloy samples were cast and subjected to surface treatments such as sandblasting, chemical etching, and sandblasting plus chemical etching. Panavia F and CandB cement were used as cementing mediums. The etching qualities were examined by a stereooptic microscope. Failure surfaces were examined throughout scanning electron microscopy. The data were evaluated using statistical methods, namely analysis of variance and multiple comparison test (Tukey HSD). Results: Significant differences were found in the bonding provided by the various cements (P < 0.001) and also type of surface treatments (P < 0.001). For all groups, sandblasted surfaces showed the highest bond strength values. There was no significant difference between the Cr-Co and the Cr-Ni alloys (P > 0.05). Conclusions: Panavia F showed higher tensile strength and the sandblasted samples possessed higher tensile strength.